Distribuição sazonal e espacial de uma comunidade de anfíbios anuros associada a uma lagoa temporária do Distrito da Lapinha, Lagoa Santa (MG) - Elias, Breno Chaves de Assis (2003)
An anuran assemblage was studied at a temporary lake situated at an open area in cerrado “lato sensu” domain at the locality of Lapinha, Municipality of Lagoa Santa, State of Minas Gerais, Brazil. Field work was carried out between January and December 2002, totaling 48 nights of observation. Naturalistic observations usually started before sunset and concluded around 23:00 hrs. Observations aiming the recording of the periods of vocalization ofthe species (three occasions) were extended from 17:00 hrs to 06:00 hrs of the day after. Twelve species of anurans, distributed among three families, were recorded at the lake: one (8,33%) represented the Bufonidae family, tive (41,67%) represented the Leptodactylidae family, and six (50,0%) represented the Hylidae family. The seasonal distribution revealed a successional process of reproductive activity among the species inhabiting the lake. It was possible to discriminate four pattems of temporal distribution: H. minuta and H. faber call during the wet and the dry seasons; L. fuscus, P. centra/is, P. cuvieri, B. paracnemis, and S. fuscovarius presented calling activity at the ending of the dry season and during the beginning of the wet season; H. ntbicundula, S. fuscomarginatus, and L. ocel/atus presented calling activity during ali wet season; and S. aff. eurydice presented calling activity only at the second half of the wet season. Ali the species present in the lake presented distinct calls. The results of the statistical analyses performed to some acoustic parameters (duration and spacing between the calls, duration and spacing between the notes, number of notes by call, and dominant frequency) revealed that the acoustic space was partitioned among the species of the community. Moreover, the seasonal and the spatial segregation were also important to the maintenance of the reproductive isolation.